REVITALISASI PERAN DEMONG ADAT DALAM TATA KELOLA PEMERINTAHAN DESA, DI DESA KENYABUR, KABUPATEN KETAPANG, KALIMANTAN BARAT - Selestinus Dimas; Indiati Indiati; Muhammad Alwiadi Pane (Nusantara Hasana Journal, 2026)
The revitalization of indigenous institutions is a strategic approach to strengthening participatory village governance based on local wisdom. This study aims to analyze the revitalization of the Demong Adat's role in village governance in Kenyabur Village, Ketapang Regency, West Kalimantan, and to examine its contribution to cultural preservation, conflict resolution, and collaboration between customary institutions and the village government. A qualitative approach employing an ethnographic method was adopted. Data were collected through participant observation, in-depth interviews with the Demong Adat, village officials, customary leaders, community leaders, and indigenous community members, as well as document analysis. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, while credibility was ensured through source and method triangulation. The findings indicate that the Demong Adat continues to possess strong social legitimacy as the guardian of customary values, mediator in conflict resolution, preserver of cultural identity, and strategic partner of the village government in deliberative decision-making. These roles contribute to social cohesion, greater community participation, and stronger village governance through the integration of indigenous values into formal administrative practices. Nevertheless, several challenges remain, including limited leadership regeneration, weak coordination between customary institutions and the village government, and declining public confidence in the consistency of customary law enforcement. The study concludes that revitalizing the role of the Demong Adat is essential for promoting inclusive, collaborative, and sustainable village governance through institutional strengthening, transparent customary governance, leadership regeneration, and the integration of local wisdom into contemporary village administration.